Analisis Pola Pertumbuhan Arsitektur Bisnis Sekolah Berdasarkan CMM - Pratiwi, Widya Wahyu; Fathoni, M. Faiz; Santoso, Arif; Yaqin, M. Ainul (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2020)
School is an educational institution established by the government / private sector with age-appropriate levels. Every school has a business process, such as the admission process for new students, the teaching and learning process by students and teachers, the process of supporting facilities for educational processes, is the pattern of every set of business process architecture in the school. Each school needs standardization which is continuously improved to match the national school standard (SSN) that has been set by the government in Government Regulation No. 19 of 2005. Good school standardization can be seen from the growing patterns of business architecture with high complexity, in mark the number of students, integrated teaching curriculum, and complete infrastructure to support school activities. So in this study, conducting an analysis of the growth patterns of business architecture in schools in order to facilitate decision making and as a reference in the education process so that schools can be well standardized, by measuring the level of maturity of the capabilities of processes in the architectural pattern of school business processes using Capability Maturity Model (CMM), the result of this study is an analysis of the growth patterns of school business architecture with the maturity of business process patterns in accordance with national school standards, which can provide information as a support in business process activities in schools